PERSONNEL INNOVATIVE POTENTIAL OF THE ENTERPRISE: STRUCTURE AND MECHANISM OF FORMATION - Rustam M. Ustaev; Valentina N. Parakhina (Вестник Северо-Кавказского федерального университета, 2022)
A definition and a systematic understanding of human innovation potential of companies. Emphasizes the importance of human innovation potential of enterprises in the innovative development of the region. Given the mechanism of formation of personnel innovative potential of the enterprise in the form of complex directions